RELATION AMONG ADIPOSITY INDEXES IN WOMAN AGED BETWEEN 45 AND 49 YEARS-OLD (Fiep Bulletin - online, 2014)
Objective: To analyze the relation between adiposity indexes in a female population. Methods: The sample was composed by 236 women aged between 45 and 49 years-old and they were visitors of the coast of Parana State. Body density was calculated by the predictive equation of JACKSON & POLLOCK (1978) with three skinfolds and fat percentage by the equation of SIRI (1961). BMI was classified by reference of WHO (1997) and waist perimeter with standardization suggested by HEYWARD and STOLARCZYK (1996). For data treatment   descriptive statistic was used; One-Way Anova and the post-hoc of Tukey among BMI groups, Pearson bivariate two-tailed correlation among adiposity indexes, (p = 0.05); and multiple regression analisys with BMI as dependent variable and fat percentage, lean body mass and age as independent variables. Results: The higher it was the mean value of BMI, the higher were systolic and diastolic resting blood pressure, body mass, waist perimeter, ? of triceps, suprailiac and abdominal skinfolds, fat percentage, fat mass and lean body mass, and all these variables were differentiated among BMI groups (p
Keywords: Relations; adiposity indexes; women